The future ecology of intelligence: AIR2IST+LaSEE2CiSEE+SEE2H3O - WANG Fei-Yue (智能科学与技术学报)
In response to the governance challenges caused by the development of artificial intelligence, a new concept or belief is proposed that "intelligent technology must be governable and will be governed". Building a future intelligent ecosystem through three major systems: achieving LaSEE→CiSEE in economic and social ecology, reducing cost of logistics and mobility and improving effectiveness and efficiency of spatiotemporal utilization; Promoting the transformation of AIR→IST paradigm shift at science and technical levels, making Control and Autonomous Science and Engineering (CASE) a new and independent interdisciplinary field for K21 education. Advocating SEE→H3O for humanistic lifestyle and human-centered technology for our well-being. Call for the use of governed intelligent technology to ensure a health and sustainable social development.